Food for the city: Framing an interdisciplinary approach for the analysis of Lisbon Metropolitan Area food system through case studies analysis. - Pinto, T.C.; Costa, P.; Marat-Mendes, T.; Henriques, C.; Borges, J.C. (12TH CITTA INTERNATIONAL CONFERENCE ON PLANNING RESEARCH, 2019)
Food security for cities and access to food for its citizens is a prerequisite that any sustainable urban development should guarantee. The Lisbon Metropolitan Area (LMA) has witnessed an extensive suburban growth mainly since the 1960’s, due to internal and external migration flows, with deep impacts on urban sustainability. Mobility, access to daily activities, such as food provision and production, and waste management in contemporary suburban areas demand for greater efforts from planning authorities, as local problematics are more and more evident for communities. The Sustainability Agenda has publicly exposed the existing inequalities which affect contemporary cities in terms of food security. Current social and economic strategies, as well as urban planning structures, seem to be inappropriate for responding to such agenda. Change is therefore required in urban planning instruments; but what changes are more pressing to deal with the food system in cities? This presentation aims to answer this question by presenting the first results of an ongoing research task which aims to identify the most relevant case-studies to approach such problematics. To do so, two key contributions are cross-referenced: first, an analysis of the integration of the food system in the Municipal Director Plans (PDM’s) of LMA, as conducted in a previous task by the SPLACH (Spatial Planning for Change) project team; second, the contributions from a concluded research project, the PERIURBAN (Peri-urban areas facing sustainability challenges: scenario development in the Metropolitan Area of Lisbon) which researched the challenges of sustainability in peripheral areas of the LMA.